Cyberbullying on Children in Victimology Perspective - Dewi Bunga; Omar Sharif Hiariej (Sociological Jurisprudence Journal, 2019)
Cyberbullying is intimidation carried out in cyberspace. Virtual space opens opportunities for cyberbullying to attack children. Children who are victims of cyberbullying tend not to report the bullying done on them. In this research, two issues will be discussed, namely the study of the victimology of cyberbullying on children and the responsibility of the State in protecting children from cyberbullying. This research is a normative juridical approach with criminal law and vicimology approach. The victimism study of cyberbullying on children shows the urgency of protecting children who are victims of cyberbullying. Cyberbulling has an impact on children's mental well-being. Those who become victims will be embarrassed, decide to quit school, feel negative feelings, even commit suicide. Judging from the possible impacts on victims, cyberbullying on children is more dangerous than bullying done in a real way, and is more dangerous than if it is done on adults. The responsibility of the State in protecting children from cyberbullying is by formulating, implementing, and forcing the rule of law on the offender. The State is also obliged to implement international commitments in preventing cyberbullying on children.